PELATIHAN PENGEMASAN SAYURAN DI PEKARANGAN PANGAN LESTARI NGONGAK TANDURAN PANGONGANGAN KOTA MADIUN - Irfan Miftahul Fauzi; Dian Ardifah Iswari; Santosa Pradana Putra Setya Negara; Ihwan Susila; Sherly Oktaviana Putri; Nailul Fadhilah (JURNAL DAYA-MAS, 2023)
Sustainable Food Yard (P2L) Ngongak Tanduran has a yard garden which grows various types of vegetables and sold in fresh form. The obstacle faced by P2L Ngongak Tanduran is old school packing. In solving the P2L Ngongak Tanduran problem, the community service team provided training modern packing various types of vegetables. After that it will provide competitive advantage and added value to vegetables. The training was held on June 26, 2023 with 2activities, namely is packing training. The results of community service activities are P2L Ngongak Tanduran can make the modern packing of vegetables.